(untitled) (Signifiances (Signifying), 2019)
Based on a redefinition of language as bodily actions, this study starts from the idea that a vocal process is organized, at the interpretation, by a spontaneous analysis consisting in particular of producing unbundling and grouping of segments, then called « signifiers ». We study here deviance phenomena from the academic prescription (unconventional unbundling and regroupings, links not ratified by the norm) in the segmentation of the signifiers. We are interested in the possible effectiveness of these deviances as motivated acts of spontaneous analysis, and in the potential relevance of segments that make these (re)analysis arise : namely, « ghost » segments superimopsed on or interposed between those expected by a conventional analysis, and the relevance of which may depend, in particular, on their inclusion in signifying networks of morphemic or sub-morphemic level. As part of the second volume of Signifying, inviting us to question the diabolicity of the symbol and the « duplicity of the sign », our purpose is thus to observe how, behind the apparent fixity of a symbolic signifier (reified as a stabilized entity, engrafted in a form delimited by borders), can hide a dia-bolic signifier, resulting from a process of analysis and construction, reconstruction, reassembly with variable geometry.